TYPICAL ARTICULATION DISORDERS - Shashiitharan Paramanantham; Wayan Westa; Nyoman Ratep (Faculty of Medicine, Udayana University, 2017)
Typical developmental disorder in which the use of sound to speak of children, are below the level corresponding to the mental age, while the corresponding rate of the normal level of language skills. Age mastery of voice to speak, and the order in which these sounds evolve show individual variation is large enough. The diagnosis is made only if the severity of articulation disorder beyond the limits of normal variation for normal mental age; intelligence (intelligence) nonverbal within normal limits; expressive and receptive language skills within normal limits; articulation disorder is not directly caused by something sensory abnormalities, structural or neurological; and one said definitely not normal in colloquial usage a day in the life of a child.Keywords: Articulation, sensory abnormalities